(untitled) (Journal of Dhaka Medical College, 2011)
Renal biopsy tissues were taken from 142 suspected glomerulonephritic patients who were admitted into the Department of Nephrology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka and Combined Military Hospital (CMH), Dhaka Cantonment, Dhaka. The tissues were processed for both Light Microscopy (LM) and Direct Immunofluorescence (DIF) studies. The study was done in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka and Armed Forces Institute of Pathology (AFIP), Dhaka Cantonment, Dhaka, from March to December 1999. Seven histopathological types of glomerulonephritis were identified with LM and another one type i.e. IgA Nephropathy was identified exclusively by using DIF. Diffuse immunofluorescence positivity was found in 44.36% cases. C3 components were found in all cases irrespective of the histopathological type of glomerulonephritis. Immune complex deposits were observed in immunofluorescence both in the mesangium and the glomerular basement membrane (GBM) with more generalized and less scattered distributions. Immunoglobulins (Ig) were tested for IgG, IgA and IgM. IgG was found the most common (74.60%) among immune complex deposits. Notable LM features include proliferation of mesangial cells, expansion of mesangial matrix, thickening of GBM, infiltration of glomerular macrophages, platelets and neutrophil and crescent formation. The presence of IgG in the mesangium of the kidney of the glomerulonephritic patient suggests a role of IgG in the inflammatory process. There is also evidence that C3 is synthesized within the glomeruli of the patients with glomerulonephritis. Finding the role of the complement components in pathogenesis of glomerulonephritis, a keen observation is needed to determine the extent of local complement synthesis and their involvement in tissue injury process. Key words: Complement synthesis; immune complex; glomerulonephritis; renal biopsy. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8566 J Dhaka Med Coll. 2011; 20(1) : 15-19